Pengaruh Gaya Kepemimpinan Dan Motivasi Kerja Terhadap Kinerja Pegawai Pada Dinas Kebudayaan Dan Pariwisata Kabupaten Tulang Bawang - Epi Parela (LPPM STIE KRAKATAU, 2018)
This study aims to reveal the influence of the influence of leadership styles and motivation to work on the performance of employees at the Department of Culture and Tourism District Onions Bones. The hypothesis proposed is: supposedly there is a positive influence between leadership style and motivation to work on the performance of employees. The research was conducted using survey methods. The entire population is at the Department of Culture and Tourism District Garlic Bones as much as 52 people, in which the sample was taken 45 people with random sampling techniques (random sampling). Research instruments based on the content validity (content validy).Instrument reliability was calculated with the formula product moment correlation, while the reliability of the instrument is calculated by the formula Alpha crobach. The results summarized as follows: t count value for the variable (X1) for 4780 (Prob.sig. = 0.000). As for the variable (X2) obtained t count for 2260 (Prob.sig. = 0.006). In the t table with a significance level of 95% (percent) (a = 5% (percent)) obtained a value of 1.671 with df = 43. Based on these values ​​is known that the t count> t-table. This shows that the coefficient of each independent variable is statistically significant independent effect on the dependent variable or in other words that the effect Significant, as well as the coefficient of determination (R2) of 63.3% (percent). Suggestions results of this study is expected to improve leadership and motivation that will affect the performance of employees at the Department of Culture and Tourism District Onions Bones. Then Coaching the employees should be improved and applied in line with objectives to improve the quality of human resources at the Department of Culture and Tourism District Onions Bones.